Finance and Development, December 2016. - International Working Group on External Debt Statistics (Washington, D.C. : International Monetary Fund, 2016)
This issue of Finance and Development examines the good and bad sides of globalization. Sebastian Mallaby notes that after decades of increasing cross-border movements of capital, goods, and people, only migration continues apace. Capital flows have collapsed, and trade has stagnated. However, rather than a sign of retreat, trade and finance may be resetting to a more sustainable level consistent with continued globalization. IMF Chief Economist Maurice Obstfeld takes a closer look at trade. Ismaila Dieng profiles Leonard Wantchekon, a former activist who plans to train the next generation of African economists. Wantchekon, now a professor at Princeton University, is one of the few African economists teaching at a top US university. His research, which has received considerable attention from development economists, focuses on the political and historical roots of economic development in Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet